Gender equality in the EU. Why we need a renewed commitment to gender mainstreaming - Jill Rubery; Valeria Insarauto; Sánchez Mira, Núria (My University, 2024)
• The European social turn following the development of the European Pillar of Social Rights and continuing through the Covid-19 pandemic and beyond produced a cluster of directives and policy programmes that were to have positive impacts on women’s labour market position. Nevertheless, this review finds that much remains to be done and identifies three main risks to gender equality that call for reinforced policy initiatives. This requires the European Union (EU) to renew and fully implement its 30-year commitment to gender mainstreaming. • The first risk is that there may be further mobilisation of women into work without a compensating increase in support for unpaid care work and changes in the household division of care work. This requires full implementation of the European Care Strategy. • The second risk arises from a failure to assess the gender equality implications of the major socioeconomic changes associated with both the green and the digital transitions. Women face potential exclusion from new green jobs and risk loss of access to standard equality rights, such as maternity leave, if the digital revolution further expands gig work. • The third risk is the threat of a further round of austerity policies. The EU and its Member States need to learn lessons from the sovereign debt crisis (Karamessini and Rubery 2014) and protect women against, for example, major cuts to care services and the devaluation of public sector jobs, in which women are concentrated. • Welcome though the social turn was and the support provided for both gender equality and a fairer labour market, there is an urgent need for a renewed commitment to gender mainstreaming to guard against negative impacts from forces for change that are often not considered to be within the scope of gender equality policies.